2017
DOI: 10.1177/1045389x17730915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atomic oxygen on epoxy-based shape memory polymer in low earth orbit

Abstract: Atomic oxygen is a dominant component of the low earth orbit and can erode most spacecraft polymeric material. In this article, the atomic oxygen erosion resistance tests of an epoxy-based shape memory polymer are carried out in a ground-based atomic oxygen simulator with a vacuum space chamber. The samples, before and after the atomic oxygen exposure, are compared in appearance, surface morphology, mass, main component, dynamical and static mechanical properties, and shape memory properties. The atomic oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…There was no change in the main characteristic peaks, as shown in Figure 3 c, i.e., the functional group did not change after AO exposure. Whether there were chemical changes was inconclusive based on these results alone, as the chemical reactions between functional groups may not be detectable with FTIR spectroscopy [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no change in the main characteristic peaks, as shown in Figure 3 c, i.e., the functional group did not change after AO exposure. Whether there were chemical changes was inconclusive based on these results alone, as the chemical reactions between functional groups may not be detectable with FTIR spectroscopy [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The temperature range in the LEO environment is between −150 °C and 150 °C, and microcracks in the matrix of the composite can be initiated by the difference in the thermal expansion coefficient of the fiber and the matrix during the thermal cycle [ 15 , 16 , 17 , 18 ]. For these reasons, the mechanical properties of polymers and polymer composites in a LEO environment have been of great interest [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Recently, researches have been conducted on surface coating and reinforcement to protect against UV and AO exposure [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leng et al. [ 157 ] also reported the effect of atomic oxygen on epoxy‐based SMPs. The results indicated that the atomic oxygen had little influence on the storage module and transition temperature, but the mechanical property decreased due to microcracks caused by atomic oxygen erosion.…”
Section: Recent Advances In Applications Of Smps and Smpcsmentioning
confidence: 99%
“…Unprotected polymers will erode at a rate of ~100 µm per year due to hyperthermal AO impinging on their surface [40]. However, AO erosion affects only the top surface layer and, therefore, has minimum or no impact on the shape memory effect (SME) of SMPs exposed to the LEO environment [41].…”
Section: Introductionmentioning
confidence: 99%